Pengaruh Self Efficacy, Pengembangan Karir Dan Self Esteem terhadap Kinerja Karyawan Yamaha Panorama Di Kota Bengkulu - Ferdianto, Diki; Arifah Hidayati; M. Noor Army (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study is to find out whether there is an influence of self-efficacy, career development and self-esteem on the performance of Yamaha Panorama in Bengkulu City. The method used in this research is distributing questionnaires. This research is a quantitative approach research. The research population was Yamaha Panorama employees in Bengkulu City, 35 samples were selected to represent Yamaha Panorama in Bengkulu City. The analytical tool used in this study uses SPSS 23. The data analysis method used is multiple linear regression. The results showed that (1) Self Efficacy has a significant effect on Yamaha Panorama Employee Performance, (2) Career Development has no significant effect on Yamaha Panorama Employee Performance, (3) Self Esteem has a significant effect on Yamaha Panorama Employee Performance, (4) Self Efficacy, Career Development and Self Esteem have a simultaneous effect on Yamaha Panorama Employee Performance.